La figura de Antonio Caballero y Góngora y su labor como «arzobispo obispo de Córdoba» = The figure of Antonio Caballero y Góngora and his work as «archbishop bishop of Córdoba» - Ruiz Carrasco, Jesús María (Hispania sacra, 2020)
This article intends to provide a necessary historiographic update and new data on the figure of Antonio Caballero y Góngora. Following previously his entire career, this study deals mainly with the work of Caballero as Bishop of Córdoba, that stood out for the introduction of the values enlightened in his Diocese, the renewal of the procedures of the curia of Córdoba and the promotion of important artistic, cultural, social and pastoral companies that marked a milestone and an example to follow for future prelates.